A Case of Neuropsychiatric Systemic Lupus Erythematosus as A Sequela of Kikuchi’s Disease - Yanto, Theo Audi; Mulia, Nathania Raphaeli; Fatah, Abraham (Medicinus, 2022)
The aetiology of Kikuchi’s Disease (KD), a benign condition associated with multiple lymph node enlargements, remains unknown but several reported cases associate it with systemic lupus erythematosus (SLE). A 34-year-old Indonesian woman presented with multiple painless lymph node enlargements around the neck with three weeks of fever, myalgia, arthralgia, night sweats, and weight loss. Laboratory examination showed pancytopenia and elevated ESR. HIV and tuberculin skin testing were negative. Lymph node biopsy confirmed the diagnosis of KD. One week later, despite improvement in lymphadenopathy, she developed fever. Her ANA, anti-Smith antibodies, and anti-Ribosomal-P protein antibodies were positive. She was diagnosed with SLE and managed as an inpatient with high dose methylprednisolone. One week later, the patient developed psychotic symptoms and fever. The results of Laboratory examinations with lumbar puncture were unremarkable. She was diagnosed with neuropsychiatric SLE (NPSLE) and managed with methylprednisolone, paracetamol, folic acid, alprazolam, and amitriptyline. One month later, the patient returned with three days of fever and dyspnea. Despite improvement in neuropsychiatric symptoms, pneumonia and tonsillopharyngitis were diagnosed based on physical examination and chest X- rays. Her condition deteriorated into septic shock. She suffered cardiac arrest and was pronounced dead, despite attempted resuscitation.While KD is a benign condition, diagnosis is challenging due to its rarity and similarity to other lymphadenopathy diseases. Its association with SLE and NPSLE carries poor prognosis with higher mortality rate from the disease progression and adverse medication effects. Thus, early intervention and prevention of complications are crucial in managing patientswith KD.